(untitled) (Research, Society and Development, 2025)
Musculoskeletal disorders (MSDs) are typically characterized by pain (often persistent) and limitations in mobility, decrease in the level of functioning and reduction in the quality of life and alternative therapeutical interventions have been studied to manage symptomatology such as laser in acupuncture points (LA). The aim of this study is to systematically review the literature of the use of LA in MSDs in pain and functional capacity. PubMed and EMBASE were systematically searched using the following terms: low-level laser therapy (LLLT) and acupuncture and ten randomized clinical trials (RCTs) that used LA in MSDs were selected. All the studies used the near-infrared PBMT irradiation, with an energy per point from 1J to 72J, power from 30 mW to 400 mW, number of sessions from 4 to 24 and application at acupuncture points according to each MSDs. Most studies have shown a significant decrease in pain and symptoms, and an increase of functionality, strength, and mobility after treatment with LA. This review demonstrates that LA produced positive effects in pain and functionality of patients with MSDs, although the evidence does not determine an effective dosage window for LA, the possible range of application adjusted and designed to fit specific musculoskeletal conditions.